Функціональне значення маркетингу у системі менеджменту підприємства - Нехай, Вікторія Василівна; Nekhai, Viktoriia (Запоріжжя : ТДАТУ, 2023)
UA: Метою статті є узагальнення досвіду впровадження та функціонального наповнення маркетингової діяльності на підприємствах для розв’язання пріоритетних завдань удосконалення управління підприємствами та розвитку економіки України. Новизна полягає в пошуку шляхів вдосконалення маркетингу в управлінні підприємством. Наведено конкретні кількісні показники, за динамікою яких можна оцінювати повноту функціонального забезпечення маркетингу, проаналізовано залежності показників діяльності підприємства. EN: Тask statement. The purpose of the article is to generalize the experience of implementation and functional filling of marketing activities at enterprises to solve the priority tasks of improving enterprise management and developing the economy of Ukraine. Research results. It is well-founded that the effectiveness of marketing depends on how responsibility for planning, sales, supply and performance of other marketing tasks is distributed in the enterprise.The shortcomings of the implementation of marketing at enterprises are indicated. In the first stages, only sales or marketing functions are transferred to the marketing service without signs of entrepreneurial initiative. There are shortcomings in the recruitment of marketers, which affects the quality of management decisions. The novelty is the search for ways to improve marketing in enterprise management. Specific quantitative indicators are given, the dynamics of which can be used to assess the completeness of marketing functionality. The dependence of the activity indicators of the "Techstat" LLC enterprise was analyzed using correlation-regression analysis. Conclusions of the analysis: the realization of products is highly dependent on the amount of marketing costs. It is argued that many domestic enterprises have not yet integrated marketing functions into the management system, so they are looking for ways to solve the problem. In case of realizing the urgent need for marketing support of the enterprise, which does not have the opportunity to create its own marketing service, they resort to the services of specialized outsourcing firms. The shortcomings of such a decision are indicated. Conclusion. Prospective for further research is the search for effective forms of marketing organization and its implementationKey words: assessment, enterprise, efficiency, management, marketing, mechanical engineering.
Functional significance of marketing in the enterprise management system
Keywords: ефективність; маркетинг; менеджмент; організація; підприємство; функція; enterprise; efficiency; management; marketing; organization; function